The Influence of Mother Tongue-Based Learning on Cognitive Learning Outcomes of Fifth Grade Students at SDN 27 Sungai Sepan in IPAS Lesson - Aprilia Tresa Wulandari; Samsul Bahri (MASI Mandiri Edukasi, 2026)
This study aims to determine the effect of mother-tongue-based learning on the learning outcomes of fifth-grade students in the IPAS subject at SDN 27 Sungai Sepan, specifically in the topic of human body anatomy. The research used a quantitative approach with a One-Group Pretest-Posttest design and involved all 11 fifth-grade students as a saturated sample. The research instruments consisted of a cognitive learning-outcome test and a questionnaire to identify students’ responses toward mother-tongue-based learning through the following indicators: (1) Students can connect everyday experiences with IPAS concepts through logical reasoning expressed in their mother tongue. (2) Students can understand more complex IPAS concepts with teacher support when explanations are delivered in their mother tongue. (3) Students actively participate in discussions and ask questions in their mother tongue to clarify IPAS concepts. Data analysis techniques included a normality test and the Wilcoxon test for non-normal data to determine whether the effect on cognitive learning outcomes was significant. The results showed that students’ cognitive learning scores improved from a pre-test average of 3.84 to a post-test average of 3.90. The Wilcoxon test results for pre-test and post-test (T table: 0 < 8) indicated that the null hypothesis (H₀) was rejected. Student responses to mother-tongue-based learning were as follows: Indicator I: 81.8%, Indicator II: 100%, Indicator III: 92.7%. It can be concluded that mother-tongue-based learning has a positive effect; the use of the Iban Sebaruk language helps students better understand IPAS concepts, demonstrating that mother-tongue-based instruction positively influences the cognitive learning outcomes of fifth-grade students at SDN 27 Sungai Sepan.